REFORMASI BIROKRASI MENUJU INDONESIA BARU, BERSIH DAN BERMARTABAT - Wardana, Data; Meiwanda, Geovani (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2017)
Changes in government patterns in Indonesia along with bureaucratic reforms, changes are needed because the governance situation contineus to shift, the old system would not fit anymore if applied in the era of Indonesia government now. Consideration and public value are the focus of this article, efforts to change the goverment bureaucracy in Indonesia to better prioritize the interest of society, would require a long process, bureucratic reform not only focusing on government action, all of the component from society and private should supported bureucratic reform so the effetive governance will be quickly achieved.